Indonesian language in the interaction among students of the two cities-Tabagsel and Sibolga - Nursyaidah; Anwar Habibi Siregar; Nasution, Leoly Ahadiathul Akhiriah (Universitas Jambi, Indonesia, 2025)
Code mixing is one of the sociolinguistic studies characterized by the mixing of two or more languages. Code-mixing events that occur can vary and are caused by various things. In the UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan learning process, code mixing cannot be avoided due to the regional origin of students studying at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. Different regional backgrounds cause code mixing among students during learning. Thus, the results of the analysis of this research show that four types of code mixing occur at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan during learning, namely: a) Word code mixing, b) Phrase code mixing, c) Clause code mixing, and d) Mixed barcode. In addition to identifying the types of code mixing, this research also uncovered the backgrounds contributing to code mixing at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, which include: a) Identification of roles (speakers and speech partners), b) Identification of varieties or styles of language features, and c) Limitations of language or terms.